Bone mineral density at the hip and its relation to fat mass and lean mass in adolescents: the Tromsø Study, Fit Futures - Winther, Anne; Jørgensen, Lone; Ahmed, Luai A.; Christoffersen, Tore; Furberg, Anne-Sofie; Grimnes, Guri; Jorde, Rolf; Nilsen, Ole-Andreas; Dennison, Elaine M.; Emaus, Nina (BMC Musculoskeletal Disorders, 2018)
Source at https://doi.org/10.1186/s12891-018-1933-x . Licensed CC BY-NC-ND 4.0. Background : Positive association between body weight and bone mass is well established, and the concept of body mass index (BMI) is associated with higher areal bone mineral density (aBMD) and reduced fracture risk. BMI, that comprises both fat mass (FM) and lean mass (LM) may contribute to peak bone mass achievement in different ways. This study explored the influence of body composition in terms of total body LM and FM on hip aBMD-values in adolescence. Methods : In 2010/2011, 93% of the region’s first-year upper-secondary school students (15–17 years old) in Tromsø, Norway attended the Tromsø Study, Fit Futures. Areal BMD at femoral neck (aBMDFN) and total hip (aBMDTH) (g/cm2), total body LM and FM (g) were measured by dual energy X-ray absorptiometry (DXA). Height and weight were measured, and BMI calculated. Lifestyle variables were collected by self-administered questionnaires and interviews, including questions on time spent on leisure time physical activity. Stratified analyses of covariance and regression models included 395 girls and 363 boys. Crude results were adjusted for age, height, sexual maturation, physical activity levels, vitamin D levels, calcium intake, alcohol consumption and smoking habits. Results : Unadjusted distribution indicated higher aBMD-levels at higher LM-levels in both genders (p < 0.001), but higher aBMD at higher FM-levels were found only in girls (p < 0.018). After multiple adjustments, aBMDFN-levels in girls were associated by 0.053 g/cm2 and 0.032 g/cm2 per standard deviation (SD) change in LM and FM (p < 0.001). Corresponding values in boys were 0.072 and 0.025 (p < 0.001). The high LM groups accounted for the highest aBMD-levels, while aBMD-levels at the LM/FM-combinations indicated different patterns in girls compared to boys. The adjusted odds ratio (95% CI) for low levels of aBMDFN was 6.6 (3.4,13.0) in boys, compared to 2.8 (1.6,4.9) in girls per SD lower LM. Conclusions : ...